Autophagy Participates in Lysosomal Vacuolation-Mediated Cell Death in RGNNV-Infected Cells - Huang, Youhua; Zhang, Ya; Liu, Zetian; Liu, Chuanhe; Zheng, Jiaying; Qin, Qiwei; Huang, Xiaohong (Frontiers in Microbiology, 2020)
Nervous necrosis viruses (NNV) was the aetiological agent of viral nervous necrosis (VNN), also referred to as viral encephalopathy and retinopathy (VER) which resulted in heavy economic losses in aquaculture industry worldwide. The dramatic cytoplasmic vacuoles were observed during NNV infection in vitro and in vivo. However, the origin and the mechanism of cytoplasmic vacuolization remained obscure. In this report, we found that cytoplasmic vacuoles morphology typically became fused and enlarged during red spotted grouper nervous necrosis virus (RGNNV) infection, accompanied by the increased cell death. Notably, Lyso-Tracker, but not Mito-Tracker or ER-Tracker was accumulated in the vacuoles, and the abnormal swelling lysosome were observed in RGNNV infected cells, suggesting that the cytoplasmic vacuoles were originated from lysosomal organelles. Cytoplasmic vacuolization and cell death in RGNNV-infected cells was completely blocked by the vacuolar H+-ATPase inhibitor (bafilomycin A1), and significantly weakened by chloroquine (CQ), a lysosomotropic agent that the acidification of the lysosomes, suggesting that lysosome acidification was essential for the formation of vacuolization. Significant inhibitory effects on vacuolization and cell death were also observed in RGNNV-infected cells after treatment with nigericin and monensin (ionophores that uncouple the proton gradient present in lysosomes), suggested that lysosome function was tightly associated with RGNNV infection induced cell death. In addition, vacuoles were found to be partly co-localized with GFP-LC3II punctate dots during RGNNV infection, and the severity of vacuolization and cell death were both significantly decreased after treatment with autophagy inhibitor 3-MA, suggested that autophagy was involved in lysosomal vacuolization and cell death evoked by RGNNV infection. Thus, our results demonstrated that autophagy participates in lysosomal vacuolation-mediated cell death during RGNNV infection, and provided new insights into understanding the potential mechanism underlying nodavirus pathogenesis in vitro.